How determinants of health determine health? - Khan, Ramsha; Qureshi, Muhammad Salman Haider (International Journal of Scientific Reports, 2018)
In this article, a broader discussion of determinants of health will be provided by giving the relevant examples, demonstrating how these determinates influence the health at individual and community level. Moreover, the definitions of the terms such as determinants of health, health inequalities and inequities, will be given. Although there are many factors that influences health, the article will focus on lifestyle, biological and environmental determinants of health. At the end a brief conclusion about the key points discussed in the essay will be provided.